(untitled)
The productive structure of the eastern region of La Pampa historically can be characterized as mixed agriculture, however, during the past two decades the area or summer crops expanded. Some studies show that the rainfall regime also varied during the same time span. This induced us lo think that there might be a causal relationship between the change in rainfall and the observed trend in the productive system. Therefore, a study or the rainfall variations during the time period 1921 to 2001 was conducted in order to evaluate their possible influence. The study area was divided into three zones: north, south and center. It was found that in all three zones the total annual rainfall during the growing season showed a positive trend. The highest proportion of rainfall increase was concentrated in the three summer months (EFM), while the lowest proportion corresponded to the winter months (JAS). During the studied period (1921 / 2001